Metagenomic Next-Generation Sequencing for the Microbiological Diagnosis of Abdominal Sepsis Patients - Li, Dongkai; Gai, Wei; Zhang, Jiahui; Cheng, Wei; Cui, Na; Wang, Hao (Frontiers in Microbiology, 2022)
Objectives. For patients with intra-abdominal infection (IAI), the rapid and accurate identification of pathogens remains a challenge. Metagenomic next-generation sequencing (mNGS) is a novel technique for infectious diseases, but its application in IAI is limited. In this study we compared the diagnostic ability of plasma mNGS with that of conventional peritoneal drainage (PD) culture in critical care settings. Methods: From January 2018 to December 2020, a prospective observational study was performed at a tertiary teaching hospital in China and data on 109 abdominal sepsis patients were collected. The pathogen detection performance of plasma mNGS and PD culture method were compared. Measurements and results: Nighty-two positive cases detected on PD culture, while plasma mNGS detected 61 positive cases. Forty-five patients (44.0%) had at least one matched pair of plasma mNGS and PD culture results. Compared with PD culture, the plasma mNGS was more rapid (27.1±4.0 vs. 68.9±22.3 hours, P<0.05). The patients received initial antibiotic treatment matched with mNGS detection showed better clinical outcomes. Conclusions. For abdominal sepsis patients, plasma mNGS can provide early, noninvasive, and rapid diagnosis. Compared with conventional PD smear, culture and blood culture methods, plasma mNGS promote the rapid detection of pathogenic bacteria.